Iowa map with Snowy Owl sightings, 1976-1977 - Black, Gladyset al (1977)
Map of Iowa Snowy Owl sightings by county, 1976-1977. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1977. Epson - sheet feed/flatbed